1998
DOI: 10.1074/jbc.273.35.22664
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ke 6, a New 17β-Hydroxysteroid Dehydrogenase, and Its Expression in Gonadal Tissues

Abstract: The abnormal regulation of the Ke 6 gene has been linked to the development of recessive polycystic kidney disease in the mouse. In this report, we have shown that Ke 6 is a 17␤-hydroxysteroid dehydrogenase and can regulate the concentration of biologically active estrogens and androgens. The Ke 6 enzyme is preferentially an oxidative enzyme and inactivates estradiol, testosterone, and dihydrotestosterone. However, the enzyme has some reductive activity and can synthesize estradiol from estrone. We find that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 39 publications
1
57
0
Order By: Relevance
“…This complex is thought to be involved in polycystic kidney disease (PKD) since aberrant expression has been found in two different models of PKD mice (Aziz et al 1993). Recently, Fomitcheva et al (1998) have found that the overexpressed protein fused with GST catalyzes efficiently the transformation of E 2 to E 1 . The transformation of testosterone to 4-dione is about 25% of that of E 2 into E 1 .…”
Section: Type 8 17 -Hsdmentioning
confidence: 99%
“…This complex is thought to be involved in polycystic kidney disease (PKD) since aberrant expression has been found in two different models of PKD mice (Aziz et al 1993). Recently, Fomitcheva et al (1998) have found that the overexpressed protein fused with GST catalyzes efficiently the transformation of E 2 to E 1 . The transformation of testosterone to 4-dione is about 25% of that of E 2 into E 1 .…”
Section: Type 8 17 -Hsdmentioning
confidence: 99%
“…Although assays of the mouse enzyme in vitro have demonstrated that it can use both E 2 and testosterone as substrates (Fomitcheva et al 1998), sequence analysis again suggests that this enzyme may primarily be involved in the regulation of fatty acid metabolism (Pletnev & Duax 2005). It is highly expressed in murine kidney and spleen, with some expression in the ovary and testes, but is significantly down-regulated in mouse models of polycystic kidney disease (Fomitcheva et al 1998). In humans, it is expressed in tissues including the liver, pancreas, kidney and skeletal muscle (Ando et al 1996).…”
Section: B-hsdsmentioning
confidence: 99%
“…17-HSD type 7 (17-HSD7) has been shown to play a role in metabolism of cholesterol (Marijanovic Z et al, 2003). 17HSD type 8 (17-HSD8) has been linked to a recessive form of polycystic kidney disease (Fomitcheva et al, 1998). Several of the 17HSD enzymes show overlap with enzymes involved in lipid metabolism (Tab.1).…”
Section: Family Members Of 17-hsdsmentioning
confidence: 99%